2004
DOI: 10.1023/b:biry.0000043542.39691.95
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection by  -Lipoic Acid in Streptozotocin-Induced Diabetes

Abstract: Glial cells provide structural and metabolic support for neurons, and these cells become reactive to any insult to the central nervous system. The streptozotocin (STZ) rat model was used to study glial reactivity and the prevention of gliosis by alpha-lipoic acid (alpha-LA) administration. The expression of glial fibrillary acidic protein (GFAP), S100B protein, and neuron specific enolase (NSE) was determined as well as lipid peroxidation (LPO) and glutathione (GSH) levels in some brain tissues. Western blot a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 16 publications
4
25
0
4
Order By: Relevance
“…Manda et al [23] observed a significant decrease in peroxidation products in X-irradiated mouse cerebellar tissue following treatment with α-lipoic acid. Baydas et al [1] demonstrated an α-lipoic acid-mediated protective effect against lipid peroxidation in the glial cells of diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Manda et al [23] observed a significant decrease in peroxidation products in X-irradiated mouse cerebellar tissue following treatment with α-lipoic acid. Baydas et al [1] demonstrated an α-lipoic acid-mediated protective effect against lipid peroxidation in the glial cells of diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, DHLA may act as a strong chain-breaking antioxidant and may enhance the antioxidant potency of other antioxidants like vitamin C in both the aqueous and in hydrophobic membrane phase 98. In addition to its antioxidant properties, LA can be neuroprotective in vivo through suppression of glial reactivity 99. Since chronic reactive gliosis exacerbates diabetic neuropathy, the administration of LA can prevent neuropathy by reducing both oxidative stress and glial hyperactivity 99.…”
Section: Nomenclature and Classification Of Antioxidantsmentioning
confidence: 99%
“…Additionally, excessive production of oxygen-free radicals and/or antioxidant deficiency to various brain regions were reported to cause morphological abnormalities and memory deficits during aging [14]. Treatment with antioxidants has been shown to protect neurons against diabetes-induced excitotoxicity and neurodegenerative conditions [15]. Additionally, diabetes is also accompanied with the marked release of inflammatory cytokines [13,16].…”
Section: Introductionmentioning
confidence: 99%